What does literature teach about digital pathology? A bibliometric study in Web of Science - López-Belmonte, Jesús; Segura-Robles, Adrián; Cho, William C.; Parra-González, María-Elena; Moreno-Guerrero, Antonio J. (IJERI: International Journal of Educational Research and Innovation, 2021)
Digital pathology (DIPA) has become an effective discipline that generates a graphic environment to diagnose and interpret the pathological information of people. When analyzing the existing literature on DIPA, a knowledge gap was produced by not reporting a study that has bibliometrically analyzed the publications on the subject. The objective of this study is to analyze the scientific production and performance achieved by the term digital pathology in the Web of Science (WoS) database. For this, a methodology based on bibliometrics has been carried out, complemented by the scientific mapping technique to search, recorder, analyze and predict the scientific literature on the state of question. We have worked with an analysis unit of 1222 documents reported from WoS database. The results show that there is no research topic in the field of study of DIPA that stands out from the rest. A conceptual gap can be observed in the thematic development, given that there is no theme that is repeated in all periods, where the connections are more thematic than conceptual. There are key documents for different topics. The main themes have been very different over the years like telepathology and artificial intelligence.